Update on implantable pacemakers. - Woodruff J; Prudente LA (Journal of Cardiovascular Nursing)
There are currently more than 3 million patients worldwide with implanted pacemakers, and indications for implants are expanding. Pacemakers today are smaller (23-30 g) and fashioned in a more physiologic shape so as to be less obtrusive. They are replete with sophisticated diagnostic and programming features that make troubleshooting of complicated arrhythmias easier. Advanced nurse clinicians need to have a basic understanding of pacemaker function, indications for implantation, an awareness of potential complications, and facility with basic troubleshooting. The purpose of this article is to describe the features of the pacemakers available today and approaches to troubleshooting these devices.